OnabotulinumtoxinA for the treatment of overactive bladder. (March 2014) - Mangera, Altaf; Chapple, Christopher R
OnabotulinumtoxinA has recently been granted a license for use in overactive bladder (OAB). This review assesses the latest evidence gained from 12 randomized-controlled trials from an updated systematic review. All randomized-controlled trials have shown significant improvements in urinary symptoms. Recent Phase III studies have also shown improvements in patient satisfaction and quality of life. Significant improvements have also been reported for urodynamic parameters. The adverse events rate is low, making this form of therapy very safe. The need for intermittent self catheterization is low overall at 12% and urinary tract infection rates are between 14 and 21%. Repeated injections have been shown to be safe up to eight injection cycles and reinjection is usually required between 6–12 months. Future studies should investigate volume, site and number of injections. Electromotive and liposome methods of administration require further study.